FXR agonist obeticholic acid induces liver growth but exacerbates biliary injury in rats with obstructive cholestasis. Issue 1 (December 2018) - Golen, Rowan; Olthof, Pim; Lionarons, Daniël; Reiniers, Megan; Alles, Lindy; Uz, Zehra; Haan, Lianne; Ergin, Bulent; Waart, Dirk; Maas, Adrie; Verheij, Joanne; Jansen, Peter; et al.
Abstract Cholestasis impairs liver regeneration following partial liver resection (PHx). Bile acid receptor farnesoid X-receptor (FXR) is a key mediator of liver regeneration. The effects of FXR agonist obeticholic acid (OCA) on liver (re)growth were therefore studied in cholestatic rats. Animals underwent sham surgery or reversible bile duct ligation (rBDL). PHx with concurrent internal biliary drainage was performed 7 days after rBDL. Animals were untreated or received OCA (10 mg/kg/day) per oral gavage from rBDL until sacrifice. After 7 days of OCA treatment, dry liver weight increased in the rBDL + OCA group, indicating OCA-mediated liver growth. Enhanced proliferation in the rBDL + OCA group prior to PHx concurred with a rise in Ki67-positive hepatocytes, elevated hepaticCcnd1 andCdc25b expression, and an induction of intestinal fibroblast growth factor 15 expression. Liver regrowth after PHx was initially stagnant in the rBDL + OCA group, possibly due to hepatomegaly prior to PHx. OCA increased hepatobiliary injury markers during BDL, which was accompanied by upregulation of the bile salt export pump. There were no differences in histological liver injury. In conclusion, OCA induces liver growth in cholestatic rats prior to PHx but exacerbates biliary injury during cholestasis, likely by forced pumping of bile acids into an obstructed biliary tree.